Respuesta :

Answer:

3[tex]\sqrt{11}[/tex] + 2[tex]\sqrt{11}[/tex] = 5[tex]\sqrt{11}[/tex]

Step-by-step explanation:

[tex]\sqrt{99}[/tex] = [tex]\sqrt{(9)(11) }[/tex] = 3 [tex]\sqrt{11}[/tex]    (separate perfect squares using factoring)

[tex]\sqrt{44}[/tex] = [tex]\sqrt{(4)(11)}[/tex] = 2 [tex]\sqrt{11}[/tex]

3 [tex]\sqrt{11}[/tex] + 2 [tex]\sqrt{11}[/tex] = 5 [tex]\sqrt{11}[/tex]   (add like terms. Think of the [tex]\sqrt{11}[/tex] like x's.)

                                        (Just add the coefficients)  

Answer:

5[tex]\sqrt{11}[/tex]

Step-by-step explanation:

Using the rule of radicals

[tex]\sqrt{a}[/tex] × [tex]\sqrt{b[/tex] = [tex]\sqrt{ab}[/tex]

Simplifying the radicals

[tex]\sqrt{99}[/tex]

= [tex]\sqrt{9(11)}[/tex]

= [tex]\sqrt{9}[/tex] × [tex]\sqrt{11}[/tex]

= 3[tex]\sqrt{11}[/tex]

-----------------------

[tex]\sqrt{44}[/tex]

= [tex]\sqrt{4(11)}[/tex]

= [tex]\sqrt{4}[/tex] × [tex]\sqrt{11}[/tex]

= 2[tex]\sqrt{11}[/tex]

Then

[tex]\sqrt{99}[/tex] + [tex]\sqrt{44}[/tex]

= 3[tex]\sqrt{11}[/tex] + 2[tex]\sqrt{11}[/tex]

= 5[tex]\sqrt{11}[/tex]

with a = 5 and b = 11